Identification of a high-affinity monoclonal antibody against ochratoxin A and its application in enzyme-linked immunosorbent assay. (November 2015) - Zhang, Xian; Sun, Mengjiao; Kang, Yue; Xie, Hui; Wang, Xin; Song, Houhui; Li, Xiaoliang; Fang, Weihuan
Abstract: Ochratoxin A (OTA) is one of the most commonly occurring mycotoxins produced by some species of Aspergillus and can contaminate cereal and cereal products. A high-affinity anti-OTA monoclonal antibody (mAb) was generated from a hybridoma cell line 2D8 using splenocytes from a BALB/c mouse immunized with synthesized OTA-bovine serum albumin conjugate. The mAb 2D8 is specific with high affinity (3.75 × 10 9  L/M). An indirect competitive ELISA (ic-ELISA) was then developed using this mAb for quantitative determination of OTA in corn and feed samples. Using the optimized conditions, there was good linearity between OTA concentration and competitive inhibition (y = −0.6076x + 0.2441, R 2  = 0.9923) with the working range from 2.4 to 23.6 μg/kg, IC50 at 7.6 μg/kg and lower limit of detection at 1.4 μg/kg. The recovery rates in spiked samples were 91.2–110.3%. Of the 56 corn and feed samples, this ic-ELISA and a commercial kit both found the same 13 samples positive for OTA with good linear correlation between the two methods in OTA quantification (R 2  = 0.9706). We conclude that this ic-ELISA can be used for rapid and quantitative screening of corn and feed samples for the presence of OTA. Highlights: A mAb 2D8 highly specific to ochratoxin A (OTA) was obtained in this study. The affinity of this anti-OTA mAb was 3.75 × 10 9  L/M. The linear range to detect OTA was 2.4–23.6 μg/kg with the IC50 of 7.6 μg/kg. This ic-ELISA showed good agreement with a commercial kit in detection of OTA.